2013
DOI: 10.3109/14992027.2012.754957
|View full text |Cite
|
Sign up to set email alerts
|

Hearing-aid use and benefit: A long-term follow-up in patients undergoing surgery for otosclerosis

Abstract: The study shows that there is an unmet need for long-term hearing rehabilitation among patients previously undergoing surgery for otosclerosis. The patients who were using hearing aids were generally very satisfied with their hearing aids, but they still reported residual activity limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“… Santa Maria et al (2013) analyzed a fairly small patient sample and also found no differences in patient satisfaction between the hybrid and nonhybrid patients. The IOI-HA scores of our patients were nearly identical to those reported by Redfors et al (2013) for patients suffering from otosclerosis who received HAs. These authors also claimed that the patients with mixed hearing loss scored better than did the patients with only sensorineural hearing loss using a HA.…”
Section: Discussionsupporting
confidence: 84%
“… Santa Maria et al (2013) analyzed a fairly small patient sample and also found no differences in patient satisfaction between the hybrid and nonhybrid patients. The IOI-HA scores of our patients were nearly identical to those reported by Redfors et al (2013) for patients suffering from otosclerosis who received HAs. These authors also claimed that the patients with mixed hearing loss scored better than did the patients with only sensorineural hearing loss using a HA.…”
Section: Discussionsupporting
confidence: 84%
“…Approximately half the cohort had a corrected hearing loss with hearing aids, (approximately half the corrected subjects had bilateral HA acquisition and half unilateral HA acquisition). Furthermore, the probability of a hearing aid increased with increased hearing loss (Redfors et al, 2013). Our use of a shortened version of the SSQ could have affected the result in the spatial and quality domain, but since the original questionnaire is based on calculations of means, it was estimated that the result would not be affected signifi cantly.…”
Section: Discussionmentioning
confidence: 99%
“…This accentuates the importance of both oral and written preoperative information, which should include all the possible risks for complications, such as sound distortion and “blocked” ear. The preoperative information seems to be one of the most important quality indicators for surgical treatment [12, 13]. In compliance with these results, a national-based preoperative patient information program has been designed, which now is available online.…”
Section: Discussionmentioning
confidence: 99%